2020
DOI: 10.1093/mnras/staa767
|View full text |Cite
|
Sign up to set email alerts
|

Testing broad-line region models with reverberation mapping

Abstract: New reverberation mapping (RM) measurements, combined with accurate luminosities and line ratios, provide strong constraints on the location of the line emitting gas in the broad line region (BLR) of active galactic nuclei (AGN). In this paper I present new calculations of radiation pressure and magnetic pressure confined clouds and apply them to a "generic AGN" and to NGC 5548. The new calculations are in good agreement with the observed lags of all broad emission lines, and with the luminosities of Lyα, C iv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 49 publications
(118 reference statements)
0
48
0
Order By: Relevance
“…This can be explained if emission from the “diffuse continuum” in the BLR is significant. The “diffuse continuum” (thermal free-bound and free-free, plus scattering) emanates from the same clouds that emit the broad emission lines ( Korista & Goad, 2001 , 2019 ; Lawther et al., 2018 ; Netzer, 2020 ). It is expected to contribute substantially to the continuum at all wavelengths but particularly around the Balmer (3646Å) and Paschen jumps (8204Å), as shown in Figure 7 .…”
Section: Uv/optical Continuum Reverberationmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained if emission from the “diffuse continuum” in the BLR is significant. The “diffuse continuum” (thermal free-bound and free-free, plus scattering) emanates from the same clouds that emit the broad emission lines ( Korista & Goad, 2001 , 2019 ; Lawther et al., 2018 ; Netzer, 2020 ). It is expected to contribute substantially to the continuum at all wavelengths but particularly around the Balmer (3646Å) and Paschen jumps (8204Å), as shown in Figure 7 .…”
Section: Uv/optical Continuum Reverberationmentioning
confidence: 99%
“…There are a few limited, and notable, cases where the AGN is near enough and the black hole massive enough that the angular size is within reach of some methods. For instance, the Event Horizon Telescope used interferometry at sub-mm wavelengths to image the black hole shadow in M87 (Event Horizon Telescope Collaboration et al, 2019), and the GRAVITY interferometer on the Very Large Telescope (VLT) has also been able to resolve the BLR in 3C 273 and IRAS 09149-6206 (Gravity Collaboration et al, 2018, 2020. However, size scales of $ 10 5 R G are currently inaccessible to all but a few AGNs; in the future, X-ray interferometry may eventually make it possible to resolve scales of a few R G in the nearest Seyfert galaxies (Uttley et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The objects are selected from the COSMOS-Legacy (e.g. Civano et al 2016, Suh et al 2015, 2020, the wide-area XMM-XXL (e.g. Georgakakis & Nandra 2011, Liu et al 2016, Menzel et al 2016), Stripe 82 X-ray survey (LaMassa et al 2016), and WISSH surveys (Bischetti et al 2017, Martocchia et al 2017, Duras et al 2017, Vietri et al 2018, and about 58% are Type-1 AGNs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Hα lag is expected to be larger than the Hβ lag due to radial stratification and optical depth effects (e.g. Rees et al 1989;Korista & Goad 2000Bottorff et al 2002;Netzer 2020). Zhang et al (2019) found the Hβ time lag of 3C 273 is fully consistent with the BLR radius measured by GRAVITY from the Paα 6 See Table 1 of Du & Wang (2019) for more details.…”
Section: Black Hole Mass and The Radius-luminosity Relationmentioning
confidence: 90%